2017
DOI: 10.1515/cerce-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sesame Seedlings to Different Concentrations of Humic Acids or Calcium Nitrate at Germination and Early Growth

Abstract: ABSTRACT. This study was conducted in order to evaluate the response of sesame seeds (Sesamum indicum L.) to organic or mineral fertilization. The effects of two fertilizers, which were calcium nitrate and humic acids were studied separately at germination and early seedlings growth. Different concentrations of humic acids (HA 0 : 0, HA 1 : 500, HA 2 : 1000 and HA 3 : 2000 mg L -1 ) or calcium nitrate (CaN 0 : 0, CaN 1 : 50, CaN 2 : 100 and CaN 3 : 200 mg L -1 ) were applied distinctly to the growth media. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…According to Wanas (2002), yeast extract has a positive effects could be explained by a stimulatory effect on cell growth and division as well as protein and nucleic acid synthesis. These outcomes concur with those mentioned by Barnett et al (1990), Nagodawithana (1991), Chen et al (1994), Zhang and Ervin (2004) and Souguir and Hannachi (2017).…”
Section: Effect Of Soaking Seed Treatments In Some Natural Substancessupporting
confidence: 91%
See 1 more Smart Citation
“…According to Wanas (2002), yeast extract has a positive effects could be explained by a stimulatory effect on cell growth and division as well as protein and nucleic acid synthesis. These outcomes concur with those mentioned by Barnett et al (1990), Nagodawithana (1991), Chen et al (1994), Zhang and Ervin (2004) and Souguir and Hannachi (2017).…”
Section: Effect Of Soaking Seed Treatments In Some Natural Substancessupporting
confidence: 91%
“…They can also increase cell membrane permeability, which is important for the transport and availability of micronutrients. In respect to Souguir and Hannachi (2017), humic acid treated at 1000 mg L -1 had the greatest speed germination index and coefficient of germination for sesame, as well as a reduction in the mean germination time. Humic acid utilisation has to be maximized, since it can quickly change into an abiotic stress that threatens plant production.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the highest germination index, the longest seedling was obtained by HA treatment. HA increased the total soluble protein content by 32% compared with the control [26]. Wafaa et al [28] reported that some chemical soil properties including soil pH, electrical conductivity (EC), organic matter and the available N, P and K increased in soil along with the application of phosphorus sources combined with a high rate of HA.…”
Section: Introductionmentioning
confidence: 99%
“…Humic acid (HA) is one of the environmentally friendly compounds used in seed priming. The HA-primed seeds were reported to enhance germination rate in chilli [18], sesame [19], wheat [20,21] and pea [22], with varying concentrations of HA and soaking time requirement for different crops. Asgharipour and Rafiei [23] reported that barley seeds primed with 0.75 g/L HA for 12 h increased seedling vigour index (SVI) compared with non-primed seeds, while Souguri and Hannachi reported significant positive results in sesame seeds primed with 1 g/L HA for 7 h [19].…”
Section: Introductionmentioning
confidence: 99%
“…The HA-primed seeds were reported to enhance germination rate in chilli [18], sesame [19], wheat [20,21] and pea [22], with varying concentrations of HA and soaking time requirement for different crops. Asgharipour and Rafiei [23] reported that barley seeds primed with 0.75 g/L HA for 12 h increased seedling vigour index (SVI) compared with non-primed seeds, while Souguri and Hannachi reported significant positive results in sesame seeds primed with 1 g/L HA for 7 h [19]. An hour of soaking with 2.5 g/L HA increased germination percentage, shoot and root growth compared with non-primed seeds of Raphanus sativus [24].…”
Section: Introductionmentioning
confidence: 99%